2017
DOI: 10.1002/ase.1705
|View full text |Cite
|
Sign up to set email alerts
|

Willingness toward organ and body donation among anatomy professors and students in Mexico

Abstract: Most anatomists agree that cadaver dissection serves as a superior teaching tool in human anatomy education. However, attitudes toward body donation vary widely between different individuals. A questionnaire was developed to determine the attitudes toward body and organ donation among those who learn the most from cadavers: medical students, medical student teaching assistants, medical students involved in research, and anatomy professors. A cross-sectional, prospective study was designed in which the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
3
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
4
31
3
4
Order By: Relevance
“…While most anatomists desire ethical consent with regards to body acquisition, difficulties to reach this level fully are still being experienced in many developing countries (Gangata, ; Quiroga‐Garza et al, ). In Nigeria, there are no state or federal laws to support donation programs (Akinola, ).…”
Section: Discussionmentioning
confidence: 99%
“…While most anatomists desire ethical consent with regards to body acquisition, difficulties to reach this level fully are still being experienced in many developing countries (Gangata, ; Quiroga‐Garza et al, ). In Nigeria, there are no state or federal laws to support donation programs (Akinola, ).…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, research has already examined the attitudes and points of view of MS towards PMBD for study and research purposes [11,12,13]. Studies on medical and healthcare students’ attitudes toward body donation have indicated that donation is mainly motivated by altruism, while the main reasons for not donating include lack of information and religious factors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diferencias profesionales en donación de cuerpos Rev Arg de Anat Clin; 2020, 12 (1): 17-22 ___________________________________________________________________________________________ www.anatclinar.com.ar La mayor parte de las publicaciones sobre el tema se basan en encuestas realizadas a docentes y profesores de Anatomía (Arraez-Aybar et al, 2010;Anyanwu and Obikili, 2012;Emue et al, 2012;Quiroga-Garza et al, 2017), quienes fueron específicamente excluidos en nuestro estudio. Saha et al (2015) public un grupo de 100 médicos, con igual cantidad de mujeres y varones, que muestra una diferencia significativa con los M de nuestro trabajo tanto para trasplante de órganos (86% -p=0,0023) como para donación del cuerpo complete (26% -p=˂0,0001).…”
Section: Discussionunclassified